Material Analysis of al-Mahārah al-Kalām in Class XII Madrasah Aliyah Teaching Books with ACTFL Standars: Analisis Materi al-Mahārah al-Kalām dalam Buku Ajar Madrasah Aliyah Berstandar ACTFL - Mahmudah; Tulus Mushtofa (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2023)
Arabic language learning textbooks have fulfilled the elements of the learning system. However, the textbooks for Arabic language learning are considered inadequate to meet students' needs and contemporary social changes. This article describes the analysis of al-mahārah al-kalām material in the Madrasah Aliyah (MA) class XII Arabic language textbook published by the Indonesian Ministry of Religion based on the American Council on the Teaching of Foreign Languages (ACTFL) guidelines. This research uses research procedures and qualitative methods. Based on a content analysis approach, this research seeks to reveal al-mahārah al-kalām learning materials for class XII MA students. al-Mahārah al-kalām was chosen as the object of study because Arabic speaking skills are highly important in a person's motivation to learn Arabic. The data analysis technique used in this research follows the content analysis method, which emphasizes a set of procedures for making valid inferences from text. Methodically, the analysis used in this research is qualitative content analysis in discourse analysis, semiotic analysis, and hermeneutic analysis. This research found three things, namely (1) the use of ACTFL as a basis for standardizing Arabic textbooks necessitates harmonization of textbook material, which so far has not been fully oriented towards ACTFL; (2) confirmation of the standardization of Arabic language learning based-on ACTFL has an impact on restructuring the curriculum for Arabic language learning. ACTFL standardization is also seen as an effort to increase Arabic language mastery globally and (3) redefinition of Arabic language learning using teaching materials for class XII MA students. This redefinition is possible to prepare students to enter the higher education market at a global level. This research confirms the significance of using ACTFL in preparing Arabic language learning textbooks at all levels of Islamic education. Future research can utilize ACTFL to analyze various basic Arabic language skills, especially in each Islamic education unit and Islamic boarding school education. Keywords: Analysis, Speaking skill, Textbook, ACTFL Abstrak Kehadiran buku ajar pembelajaran bahasa Arab dalam beberapa hal dianggap telah memenuhi unsur-unsur sistem pembelajaran, namun demikian buku-buku ajar yang saat ini berlaku dianggap kurang memadai lagi untuk memenuhi kebutuhan siswa dan kontemporarisasi perubahan sosial. Artikel ini mendeskripsikan tentang analisis materi al-mahārah al-kalām dalam buku ajar bahasa Arab Madrasah Aliyah (MA) kelas XII yang diterbitkan oleh Kementerian Agama RI berdasarkan pedoman American Council on The Teaching of Foreign Languages (ACTFL). Penelitian ini menggunakan prosedur dan cara kerja penelitian kualitatif. Dengan mendasarkan pada pendekatan content analysis, penelitian ini berupaya mengungkap materi-materi pembalajaran al-mahārah al-kalām untuk siswa MA kelas XII. al-Mahārah al-kalām dipilih sebagai objek kajian dengan pertimbangan bahwa keterampilan berbicara bahasa Arab memiliki posisi yang tinggi dari sudut motivasi seseorang belajar bahasa Arab. Teknik anlisis data yang digunakan penelitian ini mengikuti prosedur metode content analysis yang menekankan seperangkat prosedur untuk membuat inferensi yang valid dari teks. Secara metodis, analisis yang digunakan penelitian ini yaitu analisis isi kualitatif, berupa analisis wacana, analisis semiotik dan analisis hermeneutika. Penelitian ini menghasilkan tiga temuan, yaitu (1) penggunaan ACTFL sebagai basis standarisasi buku ajar bahasa Arab meniscayakan penyelarasan-penyelarasan materi buku ajar yang selama ini belum sepenuhnya beroirientasi pada ACTFL; (2) konfirmasi standarisasi pembelajaran bahasa Arab berbasis ACTFL berdampak pada penyusunan ulang kurikulum untuk pembelajaran bahasa Arab. Standarisasi ACTFL juga dipandang sebagai upaya peningkatan penguasaan bahasa Arab dalam konteks global; dan (3) redefinisi terhadap pembelajaran bahasa Arab yang menggunakan bahan ajar untuk siswa kelas XII MA. Redefinisi ini dimungkinkan dilakukan untuk menyiapkan peserta didik memasuki pasar perguruan tinggi pada tataran global. Hasil penelitian ini mengonfirmasi tentang signifikansi penggunaan ACTFL dalam penyusunan buku ajar pembelajaran bahasa Arab pada semua jenjang pendidikan Islam. Penelitian berikutnya dapat memanfaatkan penggunaan ACTFL sebagai basis analisis pada berbagai kemampuan dasar bahasa Arab, terutama pada setiap satuan pendidikan Islam dan pendidikan pesantren. Kata Kunci: Analisis, al-Mahārah al-Kalām, Buku Ajar, ACTFL